1988
DOI: 10.1111/j.1151-2916.1988.tb05861.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of High‐Temperature Creep in Silicon Carbide: III, Sintered α‐Silicon Carbide

Abstract: The operative and controlling mechanisms of steady-state creep in sintered a-Sic have been determined both from kinetic data within the ranges of temperature and constant compressive stress of 1670 to 2073 K and l38 to 414 MPa, respectively, and from the results of extensive TEM and other analytical analyses. Dislocations in glide bands, B4C precipitates, and the interaction of these two entities were the dominant microstructural features of the crept material. The stress exponent increased from 1.44 to 1.71 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 41 publications
8
37
0
Order By: Relevance
“…Based on the results, they indicated that the enhanced surface mobility of carbon atoms, which occurred at higher substrate temperatures, allowed atoms to arrange themselves into their equilibrium surface state prior to overgrowth without the 60 ° bond rotation (this rotation creates a 1111t twin boundary or stacking fault) and thus resulted in improved quality. This is also similar to the reported effect of boron on the densification of ~-SiC through the sintering process [32]. The presence of boron enhances both the lattice and grain-boundary diffusion rates to the extent that they allow full densification in the :~-SiC which densities only slightly in the pure state.…”
Section: Line and Planar Defect Density Decreasesupporting
confidence: 76%
“…Based on the results, they indicated that the enhanced surface mobility of carbon atoms, which occurred at higher substrate temperatures, allowed atoms to arrange themselves into their equilibrium surface state prior to overgrowth without the 60 ° bond rotation (this rotation creates a 1111t twin boundary or stacking fault) and thus resulted in improved quality. This is also similar to the reported effect of boron on the densification of ~-SiC through the sintering process [32]. The presence of boron enhances both the lattice and grain-boundary diffusion rates to the extent that they allow full densification in the :~-SiC which densities only slightly in the pure state.…”
Section: Line and Planar Defect Density Decreasesupporting
confidence: 76%
“…In order to assess the development of thermal stresses, and the importance of viscoelastic effects, several drilling operations on -SiC were simulated, using silicon carbide physical properties from Ramanathan and Modest [25] (all taken at removal temperatures of T re = 3000 K, which gives good agreement with variable property calculations [25]) and Edington et al [26]: k re = 20 W/mK, c re = 5 10 6 J/m 3 K, h re ' 12:1 MJ/kg, v = 10 ;6 =K; E = 400 GPa, = 0:17; and the viscoelastic properties were curve fitted to data given by Lane et al [7] as A = 5:30 10 14 =(MPa s) and Q = 840 kJ/mol. Laser parameters were typical values for a CO 2 laser (such as the one in our laboratory), using a w 0 = 175 m and an average absorbed power of P = 500 W. Several CW and pulsed laser drilling events have been simulated, including a cool-down period after the laser has been turned off, all on large wafers with a thickness of 0.7 mm (= 4w 0 ).…”
Section: Resultsmentioning
confidence: 95%
“…For example, creep rates for alumina at 1500 C have been determined by Folweiler [6]; Lane et al [7] measured creep rates for sintered -SiC, finding rates of 10 ;7 =s at 1750 C and 200 MPa. Extrapolation of these data to the melting/decomposition point indicate that plastic deformation accompanied by thermal stress relaxation is to be expected during laser shaping of ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…While the densification mechanism was not clear, it was already known that boron and carbon did not form intergranular films [5][6] but rather dissolved into the SiC grains, not supporting a liquid phase densification mechanism. High temperatures, usually above 2000 o C, are required for the solid-phase sintering.…”
Section: Introductionmentioning
confidence: 99%